Short-term shareholders, bubbles, and CEO myopia - Thanassoulis, J (University of Oxford, 2013)
This paper analyses the real economy effects of firms having some shareholders with a short investment horizon on their shareholder register. Short-term shareholders cause management to be concerned with the path of the share price as well as its ultimate value. Such shareholders in an economy lead to bubbles in the prices of key inputs, to the misallocation of firms to risky business models, and to increased costs of capital. For individual firms short-term shareholders induce the Board to reduce deferred incentives in CEO pay prompting CEO myopia and reduced investments in the long-run capabilities of the firm.